(untitled) (Stamford Journal of Pharmaceutical Sciences, 2012)
An Ethno-botanical survey was carried out among the Sugali tribes in Yerramalais of Eastern Ghats, Kurnool District, Andhra Pradesh for the exploration of antidiabetic herbal remedies. Diabetes mellitus is one of the common metabolic disorders with micro-and macrovascular complications that results in significant morbidity and mortality. It is considered as one of the five leading causes of death in the world. In Allopathy medicine no satisfactory effective therapy is still available to cure diabetes mellitus. There is increasing demand by patients to use natural products with antidiabetic activity due to side effects associated with the use of insulin and oral hypoglycemic agents. The art of herbal treatment has very deep roots in Indian culture. Even today in most of the rural areas people are depending on herbal drug systems for primary health care. The indigenous knowledge of local traditional healers and native plants used for the treatment of diabetics related health disorders were collected through questionnaire and personal interviews. A total of 10 informants with in the age group of 50 to 68 were interviewed, among them two were tribal practitioners. A total of 21 genera and 18 families were identified which are being used for the treatment of diabetes. Results depict that fresh plant materials were invariably preferred for the treatment of long term complications associated with diabetics. Anti-diabetic medicinal plants used by Sugalis have been listed along with plant parts used. The collected information’s are arranged in the alphabetic order of the plant botanical name, family with the local (or) common name, and mode of use is listed. DOI: http://dx.doi.org/10.3329/sjps.v4i2.10435 S. J. Pharm. Sci. 4(2) 2011: 19-24